Lateral orbital wall reconstruction after basal cell carcinoma penetration—Case report - Popić, Bruno; Kopić, Andrijana; Holik, Dubravka; Dinjar, Kristijan; Kopić, Vlatko; Matijević, Marko; Popić, Fran (Frontiers in Surgery, 2022)
Advanced periorbital basal cell carcinomas may necessitate orbital exenteration and consequent vision loss, which significantly reduces patients’ life quality. Orbital reconstruction is a demanding surgical procedure due to the complex orbital anatomy and vital structures located in the orbit. In this report, we presented an 83-year-old patient with advanced basal cell carcinoma that had expanded into the orbit. An orbitotomy was performed to remove the tumor completely while preserving the eye function. Orbital reconstruction was performed by a standard surgical method using a titanium mesh modeled according to a natural phantom skull. This maintained the eye function and achieved satisfactory facial esthetics.